Oleic acid-induced, controllable surface oxidation to enhance the photoresponse performance of Sb2Se3 nanorods. Issue 37 (3rd September 2020) - Guan, Fan; Li, Linjie; Cui, Yusong; Wang, Tingting; Li, Shaopeng; Li, Longhua; Zhang, Junhao; Wang, Junli
Abstract : The surface oxidation level of Sb2 Se3 nanorods is tunable by varying the volume ratio of oleic acid during the synthesis and a modest oxidation level (20–30%) is found to be favorable for the optoelectronic properties of Sb2 Se3 . Abstract : Surface oxidation frequently occurs in non-oxide antimony chalcogenides, which is a double-edged sword for their (opto)electronic properties and applications. Here we report that the photoelectronic performance of Sb2 Se3 nanorods (NRs) can be improved through an appropriate degree of surface oxidation. During the synthesis, the volume ratio of oleic acid (OA)/oleylamine (OLA) was varied to control the oxidation degrees of the Sb2 Se3 NRs, which span 1.20–51.49% with increasing OA ratio as revealed by X-ray photoelectron spectroscopy (XPS) analysis. A medium level of surface oxidation, typically 20–30% found here, is beneficial to the enhancement of the photocurrent, on/off ratios and photostability of the Sb2 Se3 NRs when evaluated in a sandwich-type ITO/Sb2 Se3 /ITO photoconductor device. Surface hydroxylation, which is boosted by the presence of Sb–oleate and trace H2 O remaining in the reaction system, is suggested to facilitate the formation of Sb–OH bonds and the OA-volume dependent oxidation at the surface of Sb2 Se3 .